2021
DOI: 10.1242/jcs.253757
|View full text |Cite
|
Sign up to set email alerts
|

Human microsporidian pathogen Encephalitozoon intestinalis impinges on enterocyte membrane trafficking and signaling

Abstract: Microsporidia are a large phylum of obligate intracellular parasites. Approximately a dozen species of microsporidia infect humans where they are responsible for a variety of diseases and occasionally death, especially in immunocompromised individuals. To better understand the impact of microsporidia on human cells, we infected human colonic Caco2 cells with Encephalitozoon intestinalis, and showed that these enterocyte cultures can be used to recapitulate the parasites’ life cycle, including the spread of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 100 publications
(108 reference statements)
5
8
0
Order By: Relevance
“…Analysis of our SBF-SEM datasets, allowed us to generate complete 3D reconstructions of the intracellular niche of E. intestinalis at 24 h and 48 h post infection (Figure 1A). Similar to recently published data [7], we found that early in infection, parasites are tightly associated with host cell mitochondria and ER (Figure 1A). We also observed that the host mitochondria were less tubular and more fragmented in infected cells, a finding that was corroborated by light microscopy (Figure 1B).…”
supporting
confidence: 92%
“…Analysis of our SBF-SEM datasets, allowed us to generate complete 3D reconstructions of the intracellular niche of E. intestinalis at 24 h and 48 h post infection (Figure 1A). Similar to recently published data [7], we found that early in infection, parasites are tightly associated with host cell mitochondria and ER (Figure 1A). We also observed that the host mitochondria were less tubular and more fragmented in infected cells, a finding that was corroborated by light microscopy (Figure 1B).…”
supporting
confidence: 92%
“…Nematodes, insects, and vertebrates all have strong transcriptional responses to infection by microsporidia, though the responses appear to be quite diverse [ 73 , 74 ]. For example, antimicrobial peptides are observed to be upregulated in silkworms and cytokines are induced in infected human cells [ 75 , 76 ]. The responses seen in these other animals are quite different than what is observed in Caenorhabditis .…”
Section: Discussionmentioning
confidence: 99%
“…Nematodes, insects, and vertebrates all have strong transcriptional responses to infection by microsporidia, though the responses appear to be quite diverse (Szumowski and Troemel, 2015; Midttun et al ., 2020). For example, antimicrobial peptides are observed to be upregulated in silkworms and cytokines are induced in infected human cells (Ma et al ., 2013; Flores et al ., 2021). The responses seen in these other animals are quite different than what is observed in Caenorhabditis .…”
Section: Discussionmentioning
confidence: 99%